azard Identification, Risk Assessment, Risk Control (HIRARC) Pada CV Jesselyne - William Edric; Togar Panjaitan (Jurnal Titra, 2023)
CV Jesselyne is a manufacturing company in the production of pillows and bolsters. Currently, the company operates without having a policy related to Occupational Safety and Health (K3). For this reason, the company wants to be able to identify potential hazard and take action to reduce the possibility of their occurrence. The study was conducted using the Hazard Identification Risk Assessment Risk Control (HIRARC) approach to meet the company’s expectations. The initial stage of the study was to conduct direct field observations along with interviews with employees working at CV Jesselyne. After analysis, from the initial conditions, 17 potential hazard were found, there in one potential hazard with an extreme risk rating, 8 potential hazard with high risk rating category, and 8 potential hazard with moderate risk rating category. If the proposals given are played by the company, there is a potential for decline hazards into 7 hazard that have a moderate risk rating value and 10 hazard that have a value low risk rating.